MyμAlbumin: A Cutting-Edge Immunoturbidity-Based Device with Real-Time and Seamless Data Transmission for Early Detection of Chronic Kidney Disease at the Point of Care - Wanna Chaijaroenkul; Napaporn Youngvises; Artitaya Thiengsusuk; Tullayakorn Plengsuriyakarn; Jakkrapong Suwanboriboon; Kridsada Sirisabhabhorn; Wanchai Meesiri; Kesara Na-Bangchang (Biosensors)
Microalbuminemia, characterized by a urinary albumin concentration between 20 and 200 mg/L, is a critical marker in assessing the risk of chronic kidney disease (CKD), diabetic nephropathy, and various other chronic conditions. Previously, we developed and validated the MyACR point-of-care (PoC) device, which facilitates the monitoring of CKD progression through real-time data transmission, thus enhancing patient management. This device utilizes a spectrophotometric dye-binding assay to measure albumin and creatinine concentrations in urine samples, providing an albumin-to-creatinine ratio (ACR) result. In the present study, we introduced a refined version of the PoC device, MyμAlbumin, designed to offer a simple, accurate, specific, sensitive, and rapid method for detecting microalbumin in urine as an early indicator of CKD and related diseases. The measurement is based on a specific immunoturbidimetric assay in a microcuvette, using a total solution volume of 125 µL (n = 5 for each validation test). The MyμAlbumin device demonstrated excellent performance, achieving high accuracy (%DMV ≤ 4.67) and precision (%CV < 5) and a strong correlation (R2 > 0.995) with laboratory spectrophotometry (dye-binding assay) and reference hospital-based immunoturbidimetric assay. Its high sensitivity (LOQ = 5 mg/L) positions MyμAlbumin as a highly viable and cost-effective tool for clinical use. Additionally, the device supports real-time, seamless data transmission, making it ideal for integration into remote healthcare settings.